Hubungan Status Gizi dengan Kejadian Anemia pada Remaja Putri - yulaeka, yulaeka (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2020)
Anemia is a condition when the levels of hemoglobin and erythrocytes are lower than normal. The normal value of hemoglobin in women is 12 -16 g / dl with erythrocytes from 3.5 to 4.5 jt / mm3. This study aimed to determine the relationship between nutritional status and Anemia of teenage girl. This research is analytic with cross sectional study design. The samples taken are 66 teenage girls, chosen by quote sampling. The data of this research used primary data obtained through checking up of body mass index and hemoglobin level. The data analysis used univariate analysis and bivariate analysis used Chi-square test. The results of this study indicate that there is a relationship between nutritional status and Anemia (p value 0.001).